2011
DOI: 10.1016/j.jtcvs.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endoscopic versus open saphenous vein harvest technique on late coronary artery bypass grafting patient outcomes in the ROOBY (Randomized On/Off Bypass) Trial

Abstract: In the ROOBY Trial, endoscopic vein harvest was associated with lower 1-year saphenous vein graft patency and higher 1-year revascularization rates, independent of the use of off-pump or on-pump cardiac surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 25 publications
3
82
0
3
Order By: Relevance
“…Despite the above advantages, there are concerns regarding the detrimental effect on vein endothelium because of stretching and pulling, and promoting thrombosis, thus leading to early graft closure. 57,58 Nevertheless, endo vein harvest is associated with less readmission, antibiotic use, wound care, and need for surgical intervention, and should be promoted over the open vein harvesting technique.…”
mentioning
confidence: 99%
“…Despite the above advantages, there are concerns regarding the detrimental effect on vein endothelium because of stretching and pulling, and promoting thrombosis, thus leading to early graft closure. 57,58 Nevertheless, endo vein harvest is associated with less readmission, antibiotic use, wound care, and need for surgical intervention, and should be promoted over the open vein harvesting technique.…”
mentioning
confidence: 99%
“…As described previously, a subgroup analysis of the ROOBY trial suggested that endoscopic vein harvesting was associated with worse outcomes (21). A secondary analysis of patients from the PREVENT IV trial at 3 years of follow-up also showed worse outcomes for patients undergoing endoscopic harvesting, but this finding has not been confirmed in other observational studies (29,31).…”
Section: Is Endoscopic Vein Harvesting Safe?mentioning
confidence: 82%
“…One major limitation of the current literature is that there is very little conclusive data regarding long-term patency rates of endoscopically harvested veins. There are some concerns that endoscopic vein harvest could be connected with a detrimental effect on vein endothelium which could promote a thrombogenic environment leading to a decrease in graft patency (Rousou et al 15 and Zenati et al 16 ). In our study, we found a statistically significant difference between the EVH and OVH groups in terms of percentage of endothelial damage which was statistically significantly higher in the EVH group.…”
Section: Discussionmentioning
confidence: 99%